Resveratrol ameliorates oxidative stress, inflammatory response and lipid metabolism in common carp (Cyprinus carpio) fed with high-fat diet - Wu, Di; Li, Jinnan; Fan, Ze; Wang, Liansheng; Zheng, Xianhu (Frontiers in Immunology, 2022)
High-fat diet is regarded as crucial inducers of oxidative stress, inflammation, and metabolic imbalance. In order to investigate the ameliorative potential of resveratrol against the progression of liver injury towards steatohepatitis, common carp (Cyprinus carpio) were distributed into six experimental groups and were fed with a normal-fat diet, a high-fat diet, and supplemented with resveratrol (0.8, 1.6, 2.4, and 3.2 g/kg diet) for 8 weeks. The high-fat diet decreased the antioxidant capacities, as well as causing the inflammatory response and lipid deposition of common carp. Resveratrol induced a marked elevation in the final body weight, weight gain rate, condition factor and significant decrease in the feed conversion ratio. Moreover, dietary resveratrol showed a significant decrease in the concentrations of alanine aminotransferase, aspartate aminotransferase, triglyceride and low-density lipoprotein, which was accompanied by an increase in HDL concentration in serum. A significant elevation in total superoxide dismutase, catalase, glutathione peroxidase and a decreased malondialdehyde content were observed, along with a substantial elevation in antioxidant activities were found. Additionally, fish fed with resveratrol had an up-regulation of hepatic catalase, copper, zinc superoxide dismutase, glutathione peroxidase 1a, and glutathione peroxidase 1b gene expression via Nrf2 signaling pathway. Expectedly, our results also demonstrated that resveratrol regulates hepatic lipid metabolism in fish by inhibiting the expression of hepatic lipogenesis genes (acetyl-CoA carboxylase 1, fatty acid synthase, and peroxisome and sterol regulatory element binding protein 1), fatty acid uptake-related genes of lipoprotein lipase, and β-oxidation-related genes of peroxisome proliferator activated receptor γ via PPAR-γ signaling pathway. Furthermore, dietary resveratrol reduced inflammation, as evident by downregulating the interleukin-1β, interleukin-6α, interleukin-8, and tumor necrosis factor-α expression levels and upregulating the interleukin-10 and transforming growth factor-β2 expression levels via NF-κB signaling pathway. As a whole, our results demonstrated that resveratrol defensed the impacts against high-fat diet on the serum biochemical, hepatic antioxidants, inflammation, and lipid metabolism.